Prdm16 Supports Arterial Flow Recovery by Maintaining Endothelial Function. Issue 1 (27th April 2021) - Craps, Sander; Van Wauwe, Jore; De Moudt, Sofie; De Munck, Dorien; Leloup, Arthur J.A.; Boeckx, Bram; Vervliet, Tim; Dheedene, Wouter; Criem, Nathan; Geeroms, Carla; Jones, Elizabeth A.V.; Zwijsen, An; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Understanding the mechanisms that regulate arterial flow recovery is important to design treatment options for peripheral artery disease patients ineligible for invasive revascularization. Transcriptional orchestrators of this recovery process represent an appealing target for treatment design. We previously identified Prdm (positive regulatory domain-containing protein) 16 as an arterial-specific endothelial transcription factor but its in vivo role in arteries remains completely unknown. Objective: To unravel the role of Prdm16 in arteries under physiological and pathological conditions, more specifically during peripheral artery disease. Methods and Results: Within the vasculature, Prdm16 expression was strictly confined to arterial endothelial and smooth muscle cells. Heterozygous loss of Prdm16 caused a modest reduction of the inner arterial diameter and smooth muscle cell coating without compromising vasomotor function. Upon femoral artery ligation, Prdm16 +/− mice featured significantly impaired flow recovery to ischemic limbs. This impairment was recapitulated in mice with a Prdm16 deletion specifically in endothelial cells ( EC-Prdm16 −/− ) but not smooth muscle cells. Structural collateral remodeling was normal in both Prdm16 +/− and EC-Prdm16 −/− mice, but significant endothelial dysfunction postligation was present in EC-Prdm16 −/− mice as evidenced by impaired endothelial-dependent relaxation. Upon ligation, endothelial Prdm16 deficiency altered the expression of genes encoding endothelial cell function regulators, many related to nitric oxide bioavailability and Ca 2+ homeostasis. Accordingly, Prdm16 overexpression in cultured endothelial cells affected both total cellular Ca 2+ levels and store-operated Ca 2+ entry. Conclusions: We showed that Prdm16 is indispensable for arterial flow recovery under pathological challenge not because it affects structural remodeling but due to its role in maintaining endothelial function. It, therefore, represents an appealing target for designing novel therapeutic strategies for no-option patients with peripheral artery disease.